Overcoming antibiotic resistance: non-thermal plasma and antibiotics combination inhibits important pathogens - Vaňková, Eva; Julák, Jaroslav; Machková, Anna; Obrová, Klára; Klančnik, Anja; Smole Možina, Sonja; Scholtz, Vladimír (Pathogens and disease, 2024)
Antibiotic resistance (ATBR) is increasing every year as the overuse of antibiotics (ATBs) and the lack of newly emerging antimicrobial agents lead to an efficient pathogen escape from ATBs action. This trend is alarming and the World Health Organization warned in 2021 that ATBR could become the leading cause of death worldwide by 2050. The development of novel ATBs is not fast enough considering the situation, and alternative strategies are therefore urgently required. One such alternative may be the use of non-thermal plasma (NTP), a well-established antimicrobial agent actively used in a growing number of medical fields. Despite its efficiency, NTP alone is not always sufficient to completely eliminate pathogens. However, NTP combined with ATBs is more potent and evidence has been emerging over the last few years proving this is a robust and highly effective strategy to fight resistant pathogens. This minireview summarizes experimental research addressing the potential of the NTP-ATBs combination, particularly for inhibiting planktonic and biofilm growth and treating infections in mouse models caused by methicillin-resistant Staphylococcus aureus or Pseudomonas aeruginosa. The published studies highlight this combination as a promising solution to emerging ATBR, and further research is therefore highly desirable.
Keywords: Animals; Pseudomonas Infections; antimicrobial resistance (AMR); combinatory therapy; cold atmospheric plasma (CAP); lidé; Mice; Drug Resistance, Microbial; Anti-Bacterial Agents; methicillin-resistant Staphylococcus aureus; methicilin rezistentní Staphylococcus aureus; bakteriální léková rezistence; myši; pseudomonádové infekce; stafylokokové infekce; modely nemocí na zvířatech; Pseudomonas aeruginosa; Disease Models, Animal; Staphylococcal Infections; biofilmy; zvířata; antibakteriální látky; Drug Resistance, Bacterial; Biofilms; plazmové plyny; antibiotická rezistence; Methicillin-Resistant Staphylococcus aureus; Plasma Gases; Humans